Sosialisasi Penggunaan Microsoft Teams Sebagai Media Pembelajaran Dalam Jaringan (Daring) - Yuniarti, Fatma (LPPPM STAI Darul Hikmah Bangkalan, 2021)
The purpose of this service is to socialize the use of the Microsoft Teams application from Microsoft Teams 365. Microsoft Teams is a modern application in the form of a hub for a team, both in small and large-scale organizations that allows users to collaborate and communicate easily wherever they are. Each user can make adjustments to add notes/other applications using the Conversation or Chat features to communicate with their co-workers. In addition, users can make edits to a document directly simultaneously without opening another application. So that everything is centered in one place. Microsoft Teams in the world of education is used as a tool to design virtual classes that make it easier for teachers and students, between teachers/students to communicate and collaborate to produce better learning outcomes. The method used in this teaching is the method used in this activity is counseling, training and mentoring. The teachers of SDN 3 Rejosari experienced a rapid increase of 93% in terms of understanding and mastery of Microsoft Teams for Education in the very good category of online learning. The cooperation as well as the motivation and enthusiasm of the SDN 3 Rejosari teachers are highly appreciated.